(untitled) (World Bulletin of Education and Learning, 2025)
This article explores the teaching of bakhshi art during the Third Renaissance and its intrinsic connection with maqom singing. Bakhshi art and the maqom school, as two branches of folk creativity, mutually influence the cultivation of the human spirit, the transmission of national values, and the development of performance culture.